LEGAL OVERVIEW OF THE REGISTRATION CERTIFICATE (STR) FOR HEALTH OFFICER - Jamaluddin Jamaluddin (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2022)
The legality of Registration Certificates (STR) for Health Workers in carrying out their duties at AM Parikesit Hospital Tenggarong is an administrative requirement that must be owned by health workers before the Covid-19 pandemic even a valid STR is an administrative requirement that must be attached when registering as a candidate for health workers in hospitals AM. Parikesit, but with the Covid-19 pandemic until now, these provisions have been relaxed and even allowed for health workers to practice without having an STR as in Circular Letter Number HK.02.01/MENKES/4394/2020 concerning Registration and Licensing of Health Workers during a Pandemic Corona virus Disease 2019 (Covid-19), there is tolerance and exceptions related to STR ownership. Therefore, the existence of these regulations provides legal certainty (legality) for RSUD AM. Parikesit currently employs health workers to serve the public who need services both related to Covid -19 and those who are not, so that the presence of health workers whose registration certificates are still in the process of being extended or who have just submitted them is legally considered legal. have a registration certificate and/or practice license. Therefore all actions of health workers in carrying out their service duties in a competent manner have authority and there is no violation of the law. The legal consequences for health workers in carrying out their duties at AM Parikesit Hospital who do not have a Registration Certificate (STR) and those who have a Registration Certificate (STR) but are not in accordance with the field of health education must be distinguished in two circumstances, namely normal conditions and emergency situations.